APLIKASI DISPOSISI SURAT DAN TELAAH STAF BERBASIS MOBILE (MOBILE LETTER) - Herpendi Herpendi; Fathurrahmani Fathurrahmani; Khairul Anwar Hafizd (Universitas Methodist Indonesia, 2022)
In facing the challenges of digitalization that is growing so rapidly, the State of Polytechnic Tanah Laut (Politala) strives to continue to adapt these developments as needed. In carrying out their duties in the field of Tri Dharma and other supporting activities, lecturers must have a clear assignment basis, as well as for educational staff. The current assignment at Politala uses a sheet of disposition paper issued by the leadership. The disposition sheet is then submitted to the General and Personnel Section as the basis for making a Letter of Assignment for the Lecturer or Tendik concerned in carrying out activities. This is risky in terms of data storage and effectiveness to efficiency in the administration of correspondence. The development of technology in the field of software is currently a solution in conducting application-based correspondence administration to facilitate archiving and data security to be effective and efficient. This study aims to develop a mobile-based application to make it easier for leaders to dispose of incoming letters to their subordinates. The disposition will provide notification to the employee concerned and can be viewed directly through the application. In addition, with applications that are built, employees can submit staff reviews and can monitor the status of their submissions in real time. This research was conducted using the prototype method and collecting data using observation and interview methods to produce a Mobile Letter application.